INTENTION TO USE M-WALLET APPLICATION: AN ADJUSTED MEASUREMENT OF FACILITATING CONDITIONS - Hendrick Hernando; Suryo Hadi Wira Prabowo; Farida Tri Hastuti (Jurnal Ekonomi dan Bisnis Airlangga)
Introduction: M-wallets have become the most prominent financial technology in Indonesia. Thus, discerning the behavioral intention of using m-wallet apps and the related determinants is essential. This study proposes an extended indicator for facilitating conditions to fill the identified gap in previous studies. The influence of facilitating conditions on usage intention is also examined.